Trapezoidal Rule Stability

Calculus Level 3

Consider the formula for trapezoidal integration of a complex exponential.

y ( t ) = y ( t Δ t ) + 1 2 [ y ˙ ( t ) + y ˙ ( t Δ t ) ] Δ t y ( t ) = e λ t y ˙ ( t ) = λ y ( t ) λ = a + j b j = 1 y(t) = y(t - \Delta t) + \frac{1}{2} \Big [ \dot{y}(t) + \dot{y}(t - \Delta t) \Big ] \, \Delta t \\ y(t) = e^{\lambda \, t} \\ \dot{y}(t) = \lambda \, y(t) \\ \lambda = a + j \, b \\ j = \sqrt{-1}

The complex exponential is processed sequentially in time with a discrete time interval Δ t \Delta t . In order for the algorithm to be stable (non-divergent) for a given Δ t \Delta t , the following condition must hold true:

y ( t ) y ( t Δ t ) 1 \large{\Big| \frac{y(t)}{y(t - \Delta t)} \Big | \leq 1}

Further, the algorithm "converges" ( y ( ) 0 ) (|y(\infty)| \approx 0) if the ratio has a magnitude less than 1 1 .

Suppose Δ t = 1 \Delta t = 1 . In terms of the ( a , b ) (a,b) plane, which of the given options best describes the trapezoidal rule "convergence region".

Full left-hand plane ( a < 0 ) (a < 0) , plus a finite area within ( a > 0 ) (a > 0) region Only a finite area within the ( a < 0 ) (a < 0) region (with the rest of the complex plane excluded) Full left-hand plane ( a < 0 ) (a < 0) , and nothing within the ( a > 0 ) (a > 0) region

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Steven Chase
May 28, 2019

Find the ratio of y ( t ) y(t) to y ( t Δ t ) y(t - \Delta t)

y ( t ) = y ( t Δ t ) + 1 2 [ y ˙ ( t ) + y ˙ ( t Δ t ) ] Δ t y ( t ) = y ( t Δ t ) + 1 2 [ λ y ( t ) + λ y ( t Δ t ) ] Δ t y ( t ) [ 1 1 2 λ Δ t ] = y ( t Δ t ) [ 1 + 1 2 λ Δ t ] y ( t ) y ( t Δ t ) = 1 + 1 2 λ Δ t 1 1 2 λ Δ t = 1 + 1 2 λ 1 1 2 λ = 1 + 1 2 ( a + j b ) 1 1 2 ( a + j b ) \large{y(t) = y(t - \Delta t) + \frac{1}{2} \Big [ \dot{y}(t) + \dot{y}(t - \Delta t) \Big ] \, \Delta t \\ y(t) = y(t - \Delta t) + \frac{1}{2} \Big [ \lambda \, y(t) + \lambda \, y(t - \Delta t) \Big ] \, \Delta t \\ y(t) \Big[ 1 - \frac{1}{2} \lambda \, \Delta t \Big ] = y(t - \Delta t) \Big[ 1 + \frac{1}{2} \lambda \, \Delta t \Big] \\ \frac{y(t)}{y(t - \Delta t)} = \frac{ 1 + \frac{1}{2} \lambda \, \Delta t }{1 - \frac{1}{2} \lambda \, \Delta t } \\ = \frac{ 1 + \frac{1}{2} \lambda }{1 - \frac{1}{2} \lambda} = \frac{ 1 + \frac{1}{2} (a + jb) }{1 - \frac{1}{2} (a + jb)} }

Both the numerator and the denominator have imaginary parts of the same magnitude. By inspection, for a < 0 a < 0 , the denominator has a larger magnitude than the numerator, yielding convergence. For a > 0 a > 0 , the numerator has a larger magnitude than the denominator, yielding divergence. Thus, the convergence region contains the entire left-hand plane a < 0 a < 0 , and none of the right-hand plane a > 0 a > 0 . For a = 0 a = 0 , the numerator and denominator have the same magnitude, but different phase angles. This results in oscillation without growth or decay.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...